Ismaili literature: a bibliography of sources and studies - Daftary, Farhad (In the United States of America and in Canada distributed by St. Martin's Press, 2004)
Ismaili Studies represents one of the most recent fields of Islamic Studies. Much new research has taken place in this field as a result of the recovery of a large number of Ismaili texts. Ismaili Literature contains a complete listing of the sources and secondary studies, including theses, written by Ismailis or about them in all major Islamic and European languages. It also contains chapters surveying Ismaili history and developments in modern Ismaili Studies